Victimization Status of Female and Male College Students in Spain: Prevalence and Relation to Mental Distress - Aizpurua, Eva (Journal of interpersonal violence, 2021)
Despite the growing body of research concerning victimization and mental health among college populations around the world, there remains a need for additional studies that emphasize the role that victimization has on mental health. This study builds on previous research by analyzing the relationship between mental distress and victimization status in Spanish college students (n = 828, 490 women and 338 men). Using online surveys, we examined the prevalence rates of seven types of victimization (threats, insults, online slander, theft, physical abuse, sexual harassment, and sexual abuse) and three mental health disorders (stress, anxiety, and depression, as measured by the DASS-21 [Depression Anxiety Stress Scale-21]) among students at two universities in southeastern Spain. According to their victimization experiences during the 12 months prior to the interviews, participants were classified into three victimization status groups: nonvictims (42.3%), single-type victims (23.3%), and polyvictims (34.4%). Except for threat and physical abuse, women reported significantly higher rates than men for each type of victimization and were classified more often as polyvictims. MANCOVA showed significant associations between polyvictimization and all three indicators of mental distress after controlling for sex. Interestingly, there were no differences between single-type victims and nonvictims in their self-reported levels of anxiety, stress, and depression. Female students reported a higher prevalence of severe and extremely severe levels of anxiety and stress than did their male counterparts. This study highlights the fact that a nontrivial proportion of college students experience mental distress, reinforces the existing link between polyvictimization and mental health disorders, and stresses the importance of violence awareness and prevention activities targeting this population.